Method for blocking cracks of hydrogen storage cap based on mineralization of microorganisms and composite materials
By using the mineralization sealing method of microorganisms and composite materials in the hydrogen storage cap layer, the problems of hydrogen diffusion and leakage caused by pore cracks in the hydrogen storage cap layer are solved, and the effect of enhancing the sealing and integrity of the cap layer is achieved, ensuring the safe storage of hydrogen.
Patent Information
- Application Number
- CN202510371674.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
The native pore cracks in the hydrogen storage cap layer cause hydrogen to diffusion and leakage, and the pressure fluctuations caused by hydrogen circulation injection and injection affect the sealing and integrity of the hydrogen storage cap layer.
A mineralized sealing method based on microorganisms and composite materials is adopted to form a dense structure to block the cracks by perfusion of fly ash fluid, composite fluid and mineralized microbial bacterial fluid.
Effectively reduce the permeability of the hydrogen storage cap layer, prevent hydrogen from diffusion and leakage, enhance the compressive, shear and disturbance resistance of the cap layer, and ensure safe storage of hydrogen.
Smart Images

Figure CN119878060A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of mineralization repair of rock formation fissures, and specifically is a method for mineralizing and plugging hydrogen storage caprock fissures based on microorganisms and composite materials. Background Art
[0002] With the major breakthroughs in my country's offshore hydrogen production technology without desalination of seawater, hydrogen, with its advantages of cleanliness, pollution-free, high efficiency and renewable, has not only promoted the important strategic development of the transformation from fossil energy to clean energy, but also the comprehensive utilization of hydrogen energy will further become an important node for mankind to transform from resource-based "energy development" to technology-based "energy creation". At the same time, due to the wide range of hydrogen explosion limits, difficulty in storage and transportation, underground large-scale hydrogen storage has gradually received attention. Underground hydrogen storage reservoirs are usually located in strata from hundreds of meters to thousands of meters. Underground hydrogen storage reservoirs usually include three types: salt caverns, aquifers and depleted oil and gas reservoirs. Depleted oil and gas reservoirs are considered to be the most potential underground hydrogen storage geological structures due to their large storage space and low degree of mining damage. my country's depleted oil and gas reservoirs are widely distributed, mainly concentrated in the northwest, north China and northeast China. Geographically, they match the oil and gas fields and the green power industry. Geologically, they have undergone comprehensive exploration and development of oil and gas, and the information is fully preserved. Surface and underground facilities can be directly put into use, reducing initial geological exploration and infrastructure investment.
[0003] However, to achieve efficient storage and extraction of hydrogen from depleted oil and gas reservoirs, the hydrogen storage caprock must have good integrity and sealing properties to prevent hydrogen from diffusing outward and causing economic losses. At the same time, the long-term storage of hydrogen and cyclic injection and production will cause fluctuations in the hydrogen storage caprock pressure, which may activate the primary pore cracks that block the migration of reservoir fluids, or cause the dredging and expansion of the primary pore structure, making the hydrogen storage caprock structure loose, becoming a potential channel for hydrogen diffusion and leakage, and affecting the stability of the reservoir. Therefore, it is very necessary to enhance the sealing and integrity of the hydrogen storage caprock through plugging, but traditional mud seals may not be able to fully penetrate and completely seal tiny pores due to the influence of water content, viscosity, etc., resulting in a low success rate of plugging. Summary of the invention
[0004] In order to solve the problems of diffusion and leakage of stored hydrogen caused by primary pores and cracks in the hydrogen storage caprock, and the pressure cycle disturbance caused by hydrogen cyclic injection and production on the sealing and integrity of the hydrogen storage caprock, the present invention provides a method for sealing hydrogen storage caprock cracks based on mineralization of microorganisms and composite materials.
[0005] The present invention adopts the following technical scheme: a method for plugging hydrogen storage cap rock cracks based on microbial and composite material mineralization, comprising: S100: injecting the prepared fly ash fluid into the hydrogen storage cap layer; S200: After the fly ash fluid is injected and the fracture structure in the hydrogen storage cap layer is fully wetted, the composite fluid composed of the prepared standard sand and granular activated carbon is injected into the hydrogen storage cap layer; S300: selecting mineralized microbial strains, activating and expanding the mineralized microbial strains in a liquid culture medium to obtain a mineralized microbial bacterial solution; S400: adding urea and calcium lactate into water to prepare a cementing solution, fully mixing the mineralized microbial solution with the cementing solution to form a mixed solution, and injecting the prepared mixed solution into the hydrogen storage cap layer; S500: simulating an actual formation environment in a laboratory, and performing steps S100 to S300 on the actual formation environment simulated in the laboratory, and replenishing a cementing fluid into the hydrogen storage cap layer according to the experimental results.
[0006] In some embodiments, in step S100, the fly ash particle size in the fly ash fluid ranges from 0.5 to 300 μm, and the density ranges from 1.4 g / cm 3 ~1.8g / cm 3 .
[0007] In some embodiments, in step S200, the particle size of the standard sand is in the range of 0.075 mm to 2 mm, the particle size of the granular activated carbon is in the range of 0.175 mm or more, and the density of the composite fluid is in the range of 1.8 g / cm 3 ~2.2g / cm 3 .
[0008] In some embodiments, in step S300, the mineralized microbial strain is selected from Sporosarcina pasteurianus.
[0009] In some embodiments, in step S400, the ratio of urea and calcium lactate in the binder liquid is 1:1, wherein urea serves as a substrate for biological metabolic reactions and calcium lactate serves as a nutrient and a Ca source.
[0010] In some embodiments, step S500 includes: S501: Select a rock sample of a larger volume in the hydrogen storage caprock as a laboratory reference object, simulate the actual formation environment in the laboratory, convert the volume of the mixed bacterial solution and the volume of the composite fluid required for injection in proportion to the exploration volume of the hydrogen storage caprock and the volume of the selected rock sample, and perform the steps S100 to S300 on the rock sample; S502: using experimental means to regularly detect the degree of cementation and repair of the bulk particles and primary cracks in the rock sample; S503: According to the rock sample implementation results, repeatedly add cementing fluid to the hydrogen storage cap layer.
[0011] In some embodiments, in step S501, the conversion formula for converting the volume of the mixed bacterial solution to be injected and the volume of the composite fluid in proportion to the volume of the hydrogen storage cap rock and the volume of the selected rock sample is as follows: Where: V1 represents the volume of hydrogen storage cap layer, m 3 ; V2 is the volume of laboratory rock sample, m 3 ; V1' represents the volume of mixed bacterial solution injected into the hydrogen storage cap layer, m 3 ; V2' represents the volume of mixed bacterial solution injected into the laboratory rock sample, m 3 ; V1'' represents the volume of composite fluid injected into the hydrogen storage cap layer, m 3 ; V2'' represents the volume of composite fluid injected into the laboratory rock sample, m 3 .
[0012] In some embodiments, step S502 includes using experimental means such as CT scanning, BET specific surface area tester, core permeability meter, etc. to regularly detect the porosity, pore size distribution, and permeability parameters of the rock sample to describe the degree of cementation and repair of the bulk particles and primary cracks in the rock sample.
[0013] In some embodiments, the hydrogen storage cap rock is the upper rock formation of a depleted oil and gas reservoir.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The method for mineralizing and plugging hydrogen storage cap cracks based on pasteurian spore Sarcina and composite fluid materials proposed in the present invention utilizes the strong cementing effect of organic matter secreted by microorganisms, which can be combined with the generated CaCO3 and adhere to the composite material and the inner wall of the crack, and gradually fill the cracks by continuously generating CaCO3 and its expansion, so that the entire cap structure becomes dense, thereby reducing the permeability of the cap, and finally achieving the goal of plugging and repairing cracks. Furthermore, the loss caused by the outward diffusion and leakage of hydrogen through the cracks in the cap is hindered. At the same time, because the hydrogen storage cap structure becomes dense, its compression resistance, shear resistance and anti-disturbance ability are enhanced, ensuring the structural safety of hydrogen address storage.
[0015] Compared with the pore plugging of traditional fluid materials such as cement and mud, the self-repairing ability of microorganisms is increased, avoiding the repeated plugging work of secondary cracks caused by pressure disturbance of the hydrogen storage cap layer after traditional plugging, and the problem that traditional plugging fluids are difficult to reach tiny pores; compared with the plugging of cracks by Bacillus pasteurianus composite rock material fluid, the urease produced by Sporosarcina pasteurianus has higher urea degradation activity and almost reaches the maximum value of known species. Sporosarcina pasteurianus is an alkaliphilic bacterium and can produce spores that are dormant for decades and survive in harsh environments for several years until cracks appear, and the cementing fluid can be injected again to activate its function.
[0016] The invention proposes to select fly ash material as the first injection fluid to plug tiny pores, which can effectively utilize the characteristics of fly ash, achieve plugging of tiny pores and fully and effectively utilize solid wastes.
[0017] The composite fluids of different particle sizes proposed in the present invention are used to seal cracks. By first injecting fly ash fluid to seal tiny pores, and then injecting standard sand and granular activated carbon composite fluids of different particle sizes to seal larger cracks, a dense "filter-type" structure of large-particle fillers to small-particle fillers in large pores and small pores can be formed, which can reduce fluid loss caused by the relatively low viscosity of the mixed bacterial liquid to a certain extent.
[0018] The composite fluids of different particle sizes proposed in the present invention for plugging cracks can realize graded use of fluids and improve material utilization. It can avoid the injection of excessive materials into the hydrogen storage cap layer caused by complete small particle filling, and can also avoid the gaps between particles caused by complete large particle filling, thereby extending the time of mineralization plugging.
[0019] The addition of activated carbon to the composite fluid proposed in the present invention can provide adsorption sites for Sporosarcina pasteurianum by utilizing its good adsorption performance, thereby reducing the number loss of Sporosarcina pasteurianum caused by flow.
[0020] Compared with the existing urea and CaCl2 formula, the urea and calcium lactate cementing solution proposed in the present invention replaces calcium lactate as bacterial nutrition and CaCl2 as raw material. 2+ Raw materials can avoid the reduction of bacterial activity and death caused by lack of nutrients in the cap rock. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of mineralization and plugging of hydrogen storage cap rock cracks by Bacillus pasteurianus and composite fluid materials; Figure 2 Flow chart of the method for mineralizing and plugging hydrogen storage cap rock cracks using Bacillus pasteurianus and composite fluid materials. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] like Figure 2 As shown, a method for plugging hydrogen storage cap rock cracks based on microbial and composite mineralization comprises: S100: injecting the prepared fly ash fluid into the hydrogen storage cap layer, which is located at a position above 800 meters underground and can be specifically described as the upper rock layer of the depleted oil and gas reservoir; Specifically, in step S100, the particle size of fly ash in the fly ash fluid is in the range of 0.5-300 μm, and the configuration density is in the range of 1.4 g / cm 3 ~1.8g / cm 3 The fly ash material is used as the first injection fluid.
[0024] S200: After the fly ash fluid is injected and the fracture structure in the hydrogen storage cap layer is fully moistened, the composite fluid composed of the prepared standard sand and granular activated carbon is injected into the hydrogen storage cap layer.
[0025] In some embodiments, in step S200, the particle size of the standard sand is in the range of 0.075 mm to 2 mm, the particle size of the granular activated carbon is in the range of 0.175 mm or more, and the concentration of the configured fluid is in the range of 1.8 g / cm 3 ~2.2g / cm 3 .
[0026] Fly ash is the fine ash collected from the flue gas after coal combustion. It is the main solid waste discharged by coal-fired power plants. A large amount of fly ash will produce dust in the air and pollute the atmosphere. If it is discharged into the water system, it will cause river siltation, and the toxic chemicals in it will cause harm to human body and organisms. Its main oxide components are: SiO2, Al2O3, FeO, Fe2O3, CaO, TiO2, etc. These active ingredients can react chemically with water to produce gelling substances, which is conducive to the sealing of fracture structures. At the same time, since the main components of fly ash are SiO2 and Al2O3, both have good hydrophilicity, and the particle size of SiO2 and Al2O3 in fly ash is extremely small, they can be adsorbed on the fracture surface of hydrogen storage cap layer, which is used to improve the wettability of hydrogen storage cap layer, which is conducive to the injection of subsequent fluids. At the same time, the Ca element contained in fly ash can provide Ca source for mineralization reaction.
[0027] S300: Sporesarcinia pasteuriana is selected as the mineralizing microbial strain, and the mineralizing microbial strain is activated and expanded in a liquid culture medium to obtain a mineralizing microbial bacterial solution.
[0028] S400: adding urea and calcium lactate into water to prepare a cementing liquid, fully mixing the mineralized microbial liquid with the cementing liquid to form a mixed liquid, and injecting the prepared mixed liquid into the hydrogen storage cap layer.
[0029] Specifically, the binder liquid contains urea and calcium lactate in a ratio of 1:1, wherein urea serves as a substrate for biological metabolic reactions and calcium lactate serves as a nutrient and a Ca source.
[0030] The strong cementing effect of the organic matter secreted by Bacillus pasteurianus can be combined with the generated CaCO3 and adhered to the composite material and the inner wall of the crack. The cracks are gradually filled by continuously producing CaCO3 and its expansion property, making the entire caprock structure dense.
[0031] The urease produced by Sporosarcina pasteurianum has a higher urea degradation activity and almost reaches the maximum value of known species. Sporosarcina pasteurianum is an alkaliphilic bacterium and can produce spores that remain dormant for decades and survive in harsh environments for several years until cracks appear, and then cementing fluid can be injected again to activate its function.
[0032] S500: simulating an actual formation environment in a laboratory, and performing steps S100 to S300 on the actual formation environment simulated in the laboratory, and replenishing a cementing fluid into the hydrogen storage cap layer according to the experimental results.
[0033] like Figure 1 As shown, the implementation of this embodiment mainly relies on the fluid and binder liquid injection device 1, which is used to apply pressure to the fluid through a pump so that it can fully reach the pore and fracture structure deep in the hydrogen storage cap layer, wherein the pipeline is used to connect the pump body and the hydrogen storage cap layer and transport the fluid.
[0034] Specifically, step S500 includes: S501: Select a rock sample from a hydrogen storage caprock with a relatively large volume as a laboratory reference object, simulate the actual formation environment in the laboratory, convert the volume of the mixed bacterial solution and the volume of the composite fluid required for injection in proportion to the volume of the hydrogen storage caprock exploration and the volume of the selected rock sample, and perform the steps S100 to S300 on the rock sample. The conversion formula is as follows: Where: V1 represents the volume of hydrogen storage cap layer, m 3 ; V2 is the volume of laboratory rock sample, m 3 ; V1' represents the volume of mixed bacterial solution injected into the hydrogen storage cap layer, m3 ; V2' represents the volume of mixed bacterial solution injected into the laboratory rock sample, m 3 ; V1'' represents the volume of composite fluid injected into the hydrogen storage cap layer, m 3 ; V2'' represents the volume of composite fluid injected into the laboratory rock sample, m 3 .
[0035] S502: using experimental means to regularly detect the degree of cementation and repair of the bulk particles and primary cracks in the rock sample; The porosity, pore size distribution, and permeability parameters of the rock samples are regularly tested using experimental methods such as CT scanning, BET specific surface area tester, and core permeability tester to describe the degree of cementation and repair of the bulk particles and primary cracks in the rock samples. The improvement in the degree of cementation and repair is reflected in the rock sample, which is manifested as a decrease in overall porosity and a pore size distribution that is mainly concentrated in micropores. As time goes by, the number of pores of various pore sizes will continue to decrease, greatly reducing the overall permeability and hindering the diffusion of fluids. When experimental monitoring finds that the cementation and repair process of the primary pores in the rock sample becomes slow, it can be determined that the cementing fluid needs to be added further.
[0036] The rate of improvement of the degree of cementation and repair of bulk particles and primary cracks in the hydrogen storage cap layer tends to decrease with time. The main reason is that the concentration of the cementing fluid inside the hydrogen storage cap layer decreases with time, the nutrients used to maintain the growth and development of microorganisms are gradually lost, the concentration of bacterial substrates used to achieve cementation and repair is reduced, and the mineralization reaction process of microorganisms stagnates. At the same time, since the laboratory reference object rock samples used in this application have a large volume, they are representative to a certain extent and can reflect the degree of cementation and repair in the actual hydrogen storage cap layer. Therefore, when experimental monitoring finds that the cementation and repair process of the primary pores in the rock sample becomes slow, it can be judged that the cementing fluid needs to be continued to be added.
[0037] S503: According to the implementation results of the rock sample, repeatedly add cementing fluid to the hydrogen storage cap layer. Combined with the implementation results of the rock sample reference object, if it is found that the porosity, permeability and other parameters of the rock sample still show large values after a long time of adding cementing fluid, there may be problems of microbial inactivation and death, and the hydrogen storage cap layer should be added in time.
[0038] After long-term biomineralization metabolism, the positions between the cracks filled with media will be blocked and connected together, making the hydrogen storage cap layer dense, thereby reducing the permeability of the hydrogen storage cap layer, hindering the passage of gas and fluid, and at the same time enhancing the mechanical properties of the hydrogen storage cap layer, which is conducive to the safe storage of hydrogen.
[0039] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for plugging hydrogen storage cap rock cracks based on microbial and composite mineralization, characterized in that: include: S100: injecting the prepared fly ash fluid into the hydrogen storage cap layer; S200: After the fly ash fluid is injected and the fracture structure in the hydrogen storage cap layer is fully wetted, the composite fluid composed of the prepared standard sand and granular activated carbon is injected into the hydrogen storage cap layer; S300: selecting mineralized microbial strains, activating and expanding the mineralized microbial strains in a liquid culture medium to obtain a mineralized microbial bacterial solution; S400: adding urea and calcium lactate into water to prepare a cementing solution, fully mixing the mineralized microbial solution with the cementing solution to form a mixed solution, and injecting the prepared mixed solution into the hydrogen storage cap layer; S500: simulating an actual formation environment in a laboratory, and performing steps S100 to S300 on the actual formation environment simulated in the laboratory, and replenishing a cementing fluid into the hydrogen storage cap layer according to the experimental results.
2. The method for plugging hydrogen storage cap rock cracks based on microbial and composite material mineralization according to claim 1, characterized in that: In step S100, the fly ash particle size in the fly ash fluid is in the range of 0.5-300 μm, and the density is in the range of 1.4 g / cm 3 ~1.8g / cm 3 .
3. The method for plugging hydrogen storage cap rock cracks based on microbial and composite material mineralization according to claim 1, characterized in that: In step S200, the particle size of the standard sand is in the range of 0.075 mm to 2 mm, the particle size of the granular activated carbon is in the range of 0.175 mm or more, and the density of the composite fluid is in the range of 1.8 g / cm 3 ~2.2g / cm 3 .
4. The method for plugging hydrogen storage cap rock cracks based on microbial and composite material mineralization according to claim 1, characterized in that: In the step S300, the mineralized microorganism strain is selected from Sporosarcina pasteurii.
5. The method for plugging hydrogen storage cap rock cracks based on microbial and composite material mineralization according to claim 1, characterized in that: In step S400, the ratio of urea and calcium lactate in the binder liquid is 1:1, wherein urea serves as a substrate for biological metabolic reactions and calcium lactate serves as a nutrient and a Ca source.
6. The method for plugging hydrogen storage caprock cracks based on microbial and composite mineralization according to claim 1, characterized in that: The step S500 includes: S501: Select a rock sample of a larger volume in the hydrogen storage caprock as a laboratory reference object, simulate the actual formation environment in the laboratory, convert the volume of the mixed bacterial solution and the volume of the composite fluid required for injection in proportion to the exploration volume of the hydrogen storage caprock and the volume of the selected rock sample, and perform the steps S100 to S300 on the rock sample; S502: using experimental means to regularly detect the degree of cementation and repair of the bulk particles and primary cracks in the rock sample; S503: According to the rock sample implementation results, repeatedly add cementing fluid to the hydrogen storage cap layer.
7. The method for plugging hydrogen storage caprock cracks based on microbial and composite material mineralization according to claim 6, characterized in that: In step S501, the conversion formula for converting the volume of the mixed bacterial solution and the volume of the composite fluid required for injection in proportion to the volume of the hydrogen storage cap rock and the volume of the selected rock sample is as follows: Where: V1 represents the volume of hydrogen storage cap layer, m 3 ; V2 is the volume of laboratory rock sample, m 3 ; V1' represents the volume of mixed bacterial solution injected into the hydrogen storage cap layer, m 3 ; V2' represents the volume of mixed bacterial solution injected into the laboratory rock sample, m 3 ; V1'' represents the volume of composite fluid injected into the hydrogen storage cap layer, m 3 ; V2'' represents the volume of composite fluid injected into the laboratory rock sample, m 3 .
8. The method for plugging hydrogen storage caprock cracks based on microbial and composite mineralization according to claim 6, characterized in that: The step S502 includes using experimental means such as CT scanning, BET specific surface area tester, core permeability tester, etc. to regularly detect the porosity, pore size distribution, and permeability parameters of the rock sample to describe the degree of cementation and repair of the bulk particles and primary cracks in the rock sample.
9. The method for plugging hydrogen storage cap rock cracks based on microbial and composite material mineralization according to claim 1, characterized in that: The hydrogen storage cap rock is the upper rock layer of the depleted oil and gas reservoir.
Citation Information
Patent Citations
Method for searching for and preventing mine water seepage of Ordovician limestone mine field
CN103643918A
Microbial seal-healing capsule for coal mine air leakage plugging as well as preparation method and application of microbial seal-healing capsule
CN107973542A
Method for reducing filtration of coal bed methane reservoir
CN108708704A
Experimental device and method for microbial remediation of reservoir guanidine gum fracturing damage
CN111350482A
Microorganism repairing agent for repairing rock cracks and preparation method of microorganism repairing agent
CN112125592A
Cited By
Modified corn straw nanocellulose as well as preparation method and application thereof
CN120943978A
System and method for repairing overlying strata water flowing fractures through microbial mineralization
CN121897406A